Efficacy and risks of anticoagulation for cerebral venous thrombosis - Xu, Weilin (Medicine (Baltimore), 2018)
BACKGROUND AND PURPOSE: Cerebral venous thrombosis (CVT) is a rare but life-threatening disease. Timely and proper treatments are the keys in saving patients’ life and preventing from permanent neurological deficits. We performed this network meta-analysis to evaluate the role of anticoagulation in CVT, especially for the patients accompanied with hemorrhagic stroke. METHODS: PubMed, Embase, Web of Science, Cochrane Database, and Chinese Biomedical (CBM) databases were searched comprehensively to select eligible articles (up to 30 June 2017). Network meta-analysis was performed based on classical frequency statistics. RESULTS: Around 14 studies comprising 1135 cases were included. Overall analysis showed that low-molecular weight heparin (LMWH) and unfractionated heparin (UFH) were more effective (LMWH vs placebo: OR 4.76, 95%CI: 2.56–8.33; UFH vs placebo: OR 4.12, 95%CI: 2.17–8.33), and safe (LMWH vs placebo: OR 0.22, 95%CI: 0.069–0.65; UFH vs placebo: OR 0.28, 95%CI: 0.058–0.99) than placebo in the management of CVT. Besides, LMWH showed more advantages than UFH; As for the patients accompanied with hemorrhagic stroke, LMWH and UFH were also better than placebo (efficacy: LMWH vs placebo: OR 20, 95%CI: 5.56–100; UFH vs placebo: OR 12.5, 95%CI: 3.7–33.3; safety: LMWH vs placebo: OR 0.18, 95%CI: 0.04–0.77; UFH vs placebo: OR 0.16, 95%CI: 0.04–0.6) in the management of CVT. In addition, LMWH was more effective than UFH for the patients accompanied with hemorrhagic stroke. CONCLUSION: Anticoagulant treatment with heparin is safe and beneficial for patients with CVT, even for those accompanied with hemorrhagic stroke. Besides, LMWH is better than UFH in the management of CVT.